Urinary tract infections in children aged 6 months to 5 years presenting with severe acute malnutrition in a tertiary care hospital - Dangayach, Naveen; Jain, Hemant (International Journal of Contemporary Pediatrics, 2021)
Background: Urinary tract infections (UTI) is more common in malnourished children than in well-nourished children. Malnutrition is associated with immune deficiency which makes affected children more vulnerable to various severe infections. World Health Organization (WHO) defined severe acute malnutrition (SAM) as weight-for-height below -3 standard deviations (or Z-scores) or mid upper arm circumference <11.5 cm or visible severe wasting or bilateral pedal edema. Methods: All eligible children were consecutively enrolled in the study. Detailed anthropometry measurements were taken and physical examination was done. Two urine specimens for routine microscopy and culture and sensitivity were sent. Antibiotic therapy was given as per standard protocol/sensitivity pattern. Statistical analysis was performed using the statistical packages for social sciences (SPSS) version 20 IBM Corporation. Results: Prevalence of UTI in our study was 21.54% in children with SAM. UTI was more common in females than males in SAM children with maximum prevalence in less than 24 months of age. MUAC was the most prevalent diagnostic criteria. Fever was the most common presenting symptom, but 36.84% asymptomatic children with SAM had UTI. Increased frequency of micturition had 100% association with UTI. E. coli was the most common isolated bacteria. Most sensitive antibiotic was imipenem. Routinely used antibiotic like ceftriaxone showed significant percentage of resistance. Conclusions: Given the high prevalence of UTI among children with SAM, it is suggested that urine culture should be performed in all children with SAM to diagnose UTI and to treat it on basis of antibiotic sensitivity pattern.